TELAAH YURIDIS TERHADAP IMPLEMENTASI PRINSIP KEHATI-HATIAN BANK DALAM AKTIVITAS PERBANKAN INDONESIA - Abubakar, Lastuti; Handayani, Tri (DE LEGA LATA: JURNAL ILMU HUKUM, 2017)
The main principle in banking activities is the prudential banking principle, which is regulated by Act No. 10/1998 on Amendment of Act No. 7/1992 concerning Banking as well as in Law No. 21/2008 concerning Sharia Banking. This prudential banking principle in practice is often normally interpreted, i.e only related to the provision of bank credit, or sometimes misinterpreted, resulting in a misperception of how and when this principle is applied in banking activities. This research uses the normative juridical approach with analytical descriptive research specification. Data were analyzed by qualitative juridical. Based on the research result, prudential banking principle must be applied starting from an institutional level, banking process, and services, including in banking credit. Banks are required to ensure compliance with regulations, including standard operating procedures issued by banks.